N-Acetyl Cysteine and Vitamin D Supplementation in Treatment Resistant Obsessive-compulsive Disorder Patients: A General Review - di Michele, Flavia; Siracusano, Alberto; Talamo, Alessandra; Niolu, Cinzia (Current Pharmaceutical Design, 2018)
Objective: Obsessive-compulsive Disorder (OCD) is a disabling mental illness for which pharmacological and psychosocial interventions are all too often inadequate. This demonstrates the need for more targeted therapeutics. Recent preclinical and clinical studies have implicated the dysfunction of glutamatergic neurotransmission in the pathophysiology of OCD. Moreover, there are studies suggesting that neuroimmune abnormalities may play an important role in the pathogenesis of OCD. N-acetyl cysteine (NAC) is a safe and readily available agent that would modify the synaptic release of glutamate in subcortical brain regions via modulation of the cysteine-glutamate antiporter. The modulation of inflammatory pathways may also play a role in the benefits seen following NAC treatment. Therefore NAC can be considered a neuroprotective agent. Methods: This paper explores the role of NAC in the treatment of OCD conditions refractory to first-line pharmacological interventions, reviewing the clinical studies published in the last decade. Results: The possible benefit mechanisms of NAC for this disorder will be discussed, as well as the role of vitamin D supplementation, given its specific property of stimulating the formation of glutathione in the brain. Conclusion: Nutraceutical supplementation in treatment resistance OCD may be important not only for improving obsessive-compulsive symptomatology, but also from a psychological perspective, given its better acceptance by the patients compared to pharmacological treatment.
Keywords: Obsessive-compulsive disorder